The development and clinical application of a novel schizophrenia screening system using yoga-induced autonomic nervous system responses - Inoue, Tomoko; Shinba, Toshikazu; Itokawa, Masanari; Sun, Guanghao; Nishikawa, Maho; Miyashita, Mitsuhiro; Suzuki, Kazuhiro; Kariya, Nobutoshi; Arai, Makoto; Matsui, Takemi (Frontiers in Physiology, 2022)
Background In severe cases, schizophrenia can result in suicide and social isolation. Diagnosis delay can lead to worsening symptoms, and often results in prolonged therapy. An estimated 50%–80% of patients with schizophrenia are unaware of their condition. Biomarkers for schizophrenia are important for receiving a diagnosis from a psychiatrist at an early stage. Although previous studies have investigated near-infrared spectroscopy as a biomarker for schizophrenia, the required equipment is expensive and not designed for home use. Hence, we developed a novel home-use schizophrenia screening system that uses a wearable device to measure autonomic nervous system responses induced by yoga, which is frequently adopted in rehabilitation for schizophrenia. Materials and Methods The schizophrenia screening system automatically distinguishes patients with schizophrenia from healthy subjects via yoga-induced transient autonomic responses measured with a wearable wireless electrocardiograph (ECG) using linear discriminant analysis (LDA; Z score ≥ 0 → suspected schizophrenia, Z-score < 0 → healthy). The explanatory variables of LDA are averages of four indicators: components of heart rate variability (HRV): the very low-frequency (VLF), the low-frequency (LF), HR, and standard deviation of the NN intervals (SDNN). In the current study, HRV is defined as frequency domain HRV, which is determined by integrating RRI power spectrum densities from 0.0033 Hz to 0.04 Hz (VLF) and 0.04 Hz to 0.15 Hz (LF), and as time domain HRV, SDNN of which is calculated as the mean of the standard deviations of the RR intervals. These variables were measured before (5 minutes), during (15 minutes), and after (5 minutes) yoga in a 15-minute mindfulness-based yoga program for schizophrenia. The General Health Questionnaire-28 (GHQ28) score was used to assess the severity of mental disorders for patients and healthy volunteers. Twelve patients (eight female and four male, 23–60 years old) and 16 healthy volunteers (seven female and nine male, 22–54 years old) were recruited. Results The schizophrenia screening system achieved sensitivity of 91% and specificity of 81%. Z-scores of LDA were significantly correlated with GHQ28 scores (r = 0.45, p = 0.01). Conclusion: Our proposed system appears to be promising for future automated preliminary schizophrenia screening at home.